Virtual Laboratories in Science Learning: Challenges and Opportunities - Gunawan, Gunawan; Herayanti, Lovy; Imran, Imran; Rahmatullah, Rahmatullah; Fathoroni, Fathoroni (Indonesian Journal of STEM Education, 2023)
This review article examines the use of virtual laboratories in science education, highlighting the associated challenges and opportunities. Through a literature analysis, this article explores the potential of virtual laboratories to enhance understanding of scientific concepts, develop practical skills, and provide accessibility to learning. Conversely, this article also discusses implementation challenges, such as issues of validity, effective interface design, and the need for technological support. In conclusion, this article provides insights into how virtual laboratories can be optimized to deliver meaningful and effective science learning experiences.